Financial shenanigans : How to detect accounting gimmicks and fraud in financial reports - Schilit, Howard Mark (New York, N.Y. : McGraw-Hill, 2002)
Pulling back the curtain on the current climate of accounting fraud, this book presents tools that anyone who is potentially affected by misleading business valuations can use to research and read financial reports, and to identify early warning signs of a company's problems.
Includes index.
oif 13/03/15
Loan
Keywords: Fraud; Misleading financial statements